Hypoxia-inducible factors: where, when and why? - Gleadle, J; Mole, D; Pugh, C (2006)
Hypoxia-inducible factor (HIF) is a family of transcription factors that regulate the homeostatic response to oxygen deprivation during development, physiological adaptation, and pathological processes such as ischemia and neoplasia. Our understanding of the function of different HIF isoforms is being advanced by understanding the processes that regulate their activity, learning where and when they are expressed and what genes they regulate.